Effect of Irrigation, Variety and Nitrogen on Growth and Productivity of Wheat (Triticum aestivum L.) in the Lateritic Belt of West Bengal - Malik, G. C.; Iftikar, Wasim; Banerjee, M.; Ghosh, D. C. (International Journal of Bio-resource and Stress Management, 2012)
A field experiment was conducted at Sriniketan to study the performance of wheat (Triticum aestivum L.) varieties under limited nitrogen and water supply in red and lateritic belt of West Bengal. The experiment was laid out in a split plot design with irrigation levels (no irrigation and three irrigations at Crown root initiation stage (CRI), heading and soft dough stages) as the main plots and crop varieties (Sonalika and UP 262) and nitrogen levels (50 and 100 kg ha-1) combinations in the sub plots. Results indicated that irrigation had significant influence on dry matter accumulation, leaf area index, no of earheads m-2, number of grains per earhead and test weight of grain that ultimately led to high grain and straw yield and harvest index. Significant response of nitrogen was also obtained on all the growth and yield parameters along with grain and straw yield and harvest index. UP 262 showed higher LAI at heading and greater number of grains per earhead and finally produced higher grain yield and harvest index. Nitrogen level (100 kg ha-1) with three irrigations at CRI, heading and soft dough stages may be followed for obtaining high grain yield of wheat variety UP 262 in lateritic belt of West Bengal.